Nifedipine-induced histological changes in the parotid glands of hypertensive rats - Seferos,Nikos (2014)
Nifedipine is a widely used anti-anginal and anti-hypertensive agent. It is associated with significant gingival changes attributed more to collagen hyperplasia than to enhancement of protein synthesis. We investigated the influence of nifedipine on morphological changes in the parotid glands of rats in a model of hypertension. Twenty-eight male Wistar rats (8–10 weeks; 200 ± 15 g) were divided into four groups (A–D). Hypertension was induced by surgical means in groups C and D. Animals in groups B and D were treated with nifedipine (0.85 mg/kg) via a gastroesophageal catheter the day after surgery (experimental day-1) for 2 weeks. A significant difference was observed between the control group and nifedipine group and between the control group and hypertension group with regard to the weight of the parotid gland and its surface area. Histological findings demonstrated changes in the parotid glands of hypertensive animals with mild vessel dilatation and infiltration of inflammatory cells. These histological findings seemed to be due more to changes in venous function than to alterations in gland architecture.